Perfectionism, intolerance of uncertainty and coping in relation to fear of cancer recurrence in breast cancer patients. Issue 4 (13th February 2023) - Blom, Mariska; Guicherit, Onno R.; Hoogwegt, Madelein T.
Abstract: Objective: Improved medical treatment has led to an increased cohort of cancer survivors. The prevalence of emotional problems in this group is high, with fear of cancer recurrence (FCR) being among the most prevalent and distressing conditions. In order to gain more insight in the psychological mechanisms playing a role in levels of FCR, this study examined the relationship between perfectionism and FCR in breast cancer patients, as well as the mediating role of intolerance of uncertainty (IU) and coping in this relationship. In order to contribute to a more comprehensive understanding of the mechanisms related to the experience of FCR in breast cancer patients, the purpose of the present study is to investigate the relationship between perfectionism and FCR, with IU and coping strategies as possible mediating factors. Methods: Validated Dutch versions of the FCR Inventory, the Multidimensional Perfectionism Scale, the Intolerance of Uncertainty Scale and the Utrechtse Coping List were filled out by 146 breast cancer patients, at least one year after (finishing) medical treatment. Correlation analyses were conducted to administer the associations between FCR, perfectionism, IU, coping and demographic/medical variables. PROCESS was used to examine mediation mechanisms. Results: A significant correlation was found between perfectionism and FCR ( r  = 0.19, p  = 0.024). IU was found to mediate the relationship between perfectionism and FCR. In contrast, coping style did not emerge as a significant mediating factor. Conclusions: This study shows that intolerance of uncertainty mediates the relationship between perfectionism and FCR. Psychological interventions targeting FCR may benefit from incorporating specific modules on dealing with uncertainty. Future research is necessary to further increase understanding of the mechanisms that play a role in FCR, in order to optimize and personalize psychological treatment for cancer patients with this type of emotional distress.